2018
DOI: 10.1101/410183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Full-length transcript characterization of SF3B1 mutation in chronic lymphocytic leukemia reveals downregulation of retained introns

Abstract: SF3B1 is one of the most frequently mutated genes in chronic lymphocytic leukemia (CLL) and is associated with poor patient prognosis. While alternative splicing patterns caused by mutations in SF3B1 have been identified with short-read RNA sequencing, a critical barrier in understanding the functional consequences of these splicing changes is that we lack the full transcript context in which these changes are occurring. Using nanopore sequencing technology, we have resequenced full-length cDNA from CLL sample… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 46 publications
1
76
0
Order By: Relevance
“…FLAIR is another recent pipeline designed to identify and quantify transcripts in long-read PacBio or ONT data 39 . To compare FLAIR and TALON, we ran FLAIR on the full-length, non-chimeric PacBio reads from GM12878 replicates 1 and 2 as described in the Supplementary Methods.…”
Section: Comparison Of Talon and Flair On Gm12878 Pacbio And Ont Datamentioning
confidence: 99%
“…FLAIR is another recent pipeline designed to identify and quantify transcripts in long-read PacBio or ONT data 39 . To compare FLAIR and TALON, we ran FLAIR on the full-length, non-chimeric PacBio reads from GM12878 replicates 1 and 2 as described in the Supplementary Methods.…”
Section: Comparison Of Talon and Flair On Gm12878 Pacbio And Ont Datamentioning
confidence: 99%
“…However, long-read sequencing approaches offered by PacBio and Oxford nanopore are continually improving sequencing throughput and quality. Recent studies using newer Nanopore flow cell chemistry and higher-throughput platforms have demonstrated data yield orders of magnitude greater than this study (Tang et al, 2018). With greater data yield and improved transcriptome coverage, there is the potential to identify more U2AF1 S34F dysregulated isoforms with greater confidence.…”
Section: Discussionmentioning
confidence: 75%
“…Total RNA was extracted from whole cell lysate using Zymo Direct-zol RNA kits. Purified RNA was prepared for long-read following previously established protocols (Picelli et al, 2013;Byrne et al, 2017;Tang et al, 2018). Total RNA was reverse transcribed using the SmartSeq2 protocol, and amplified using 15 cycles of PCR.…”
Section: Data Generation and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-read sequencing provides accurate full-length isoform structures, but suffers from a relatively high sequencing error rate that leads to spurious splice junction detection 41 . Conversely, short-read sequencing relies on the error-prone computational reconstruction of short reads into transcript models, but has highly accurate splice junction detection 32 .…”
Section: Defining a Hybrid Transcriptomementioning
confidence: 99%